29th IEEE Conference on Decision and Control 1990
DOI: 10.1109/cdc.1990.203775
|View full text |Cite
|
Sign up to set email alerts
|

Time optimal trajectories for cooperative multi-robot systems

Abstract: In this paper we describe a methodology to determine the time-optimal trajectories for cooperative multimanipulator systems (CMMS). The dynamics of CMMS and the joint torque constraints and the constraints on the intemal forces and the distribution of the payload are incorporated into our algorithm. Linear programming techniques are utilized to find the admissible phase plane boundary. Once the admissible phase plane region is found, the actual CMMS time-optimal trajectory can be constructed by employing simil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 8 publications
0
19
0
Order By: Relevance
“…[5], and linear programming approach was used to determine the trajectories. Both Moon and Ahmad [4] and Bobrow et. al.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[5], and linear programming approach was used to determine the trajectories. Both Moon and Ahmad [4] and Bobrow et. al.…”
mentioning
confidence: 99%
“…In this paper we first summarize the general time-optimal trajectory planning method for cooperative multi-manipulator system as presented before [4]. In this approach, linear programming techniques are used to find the extreme value of the acceleration we can obtain from the given dynamic equations and force torque constraints.…”
mentioning
confidence: 99%
“…We can express the end-effector forceFi which is expressed in the i-th base coordinate frame as the resultant force Fi in the object coordinate system attached at the center of mass of the carried object, as seen in Figure 1. where Bi was defined by equation (3). Therefore, equation (2) can be simplified as follows.…”
Section: Manipulator Systemmentioning
confidence: 99%
“…It was shown that linear programming could be used to find the trajectory speed-up factor in order to minimize the traversal time under the given velocity profile. The true timeoptimal trajectory planning of CMMS when the desired path is known in advance has been studied dently both by Moon and Ahmad [3] and Bobrow et.…”
Section: Introductionmentioning
confidence: 99%
“…( 11) under the boundary conditions, eqs. (8) and (9) and joint torques/forces constraints, eq. ( 10).…”
Section: Search Of X(s)mentioning
confidence: 99%